2020
DOI: 10.1108/mip-02-2019-0072
|View full text |Cite
|
Sign up to set email alerts
|

Repurchase intentions in Y generation: mediation of trust and e-satisfaction

Abstract: PurposeResearch on online businesses has focused on the adoption of e-commerce and initial purchase behavior; repurchase intention and its antecedents remain underresearched. The present study develops an empirical model to explore the extent to which trust and e-satisfaction mediate the effect of vendor-specific attributes and customer intention to repurchase from the same online platform.Design/methodology/approachThe proposed model is tested and validated in the context of Generation Y in India. A self-admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(168 citation statements)
references
References 58 publications
9
73
0
17
Order By: Relevance
“…Pointing the difference of repurchase intention among different generations, many studies argued that, the repurchase intention of Gen Y is different from Gen X ( Soares et al., 2017 ; Trivedi and Yadav, 2020 ). These studies have noted that Gen Y are comfortably get information about prices, brands, and experiences of others in shopping.…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…Pointing the difference of repurchase intention among different generations, many studies argued that, the repurchase intention of Gen Y is different from Gen X ( Soares et al., 2017 ; Trivedi and Yadav, 2020 ). These studies have noted that Gen Y are comfortably get information about prices, brands, and experiences of others in shopping.…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…This research aims to bridge the gap in the existing literature by proposing service quality as the factor that could influence mobile shoppers' behaviour. Various researchers have revealed that service quality has a positive relationship with satisfaction is shown by several studies (Trivedi & Yadav, 2020;Adekunle & Ejechi, 2018). Trivedi and Yadav (2020) found that service quality was positively associated with satisfaction.…”
Section: Service Quality (Sq)mentioning
confidence: 99%
“…Understanding customer RI is beneficial because satisfied customers tend to continue their relationship with certain sellers rather than dissatisfied (Ibzan et al, 2016). In the existing literature, RI has been discussed in service context (Trivedi & Yadav, 2020;Adekunle & Ejachi, 2018). Trivedi & Yadav (2020) found that consumers RI has a significantly affect on consumer buying behaviour in e-commerce.…”
Section: Repurchase Intention (Ri)mentioning
confidence: 99%
See 2 more Smart Citations